A MEDIUM VOLTAGE 2O KV DISTRIBUTION LINE SECURTY SYSTEM BASED LIGHTNING SUN PT. PLN (PERSERO) ULP PERDAGANGAN - Jeki Irwanda; Hamdani Hamdani; Adi Sastra P Tarigan (INFOKUM, 2022)
Feeders PRD.01 a distribution channel 20 kV medium voltage substations sourced from Pesanggaran and serve consumers of electricity in the area and surrounding Perdagangan. Perdagangan Feeders mostly through the coastal areas. According to data obtained from the BMKG, lightning phenomenon that occurs with the maximum number of strikes per month to more than 6000 lightning to the ground and more than 1000 lightning to the cloud. Based on data PT PLN (Persero) ULP Perdagangan , during the period of 2010 feeders Perdagangan experienced 12 times lightning surge disturbances resulting feeders off (trip). Reduce the occurrence of interruptions of feeders and reduce damage to equipment in medium voltage distribution lines caused by lightning on surja. Wire ground attacks on medium voltage air channels combined with lightning arrester along 12 ,45 miles on air duct medium voltage. Ground wire serves as the main seat in medium voltage distribution channels against disruption while lightning strikes lightning arrester serves to protect the network from intrusion when lightning strikes the ground wire failed in protecting the chain lightning arrester will back up work from the ground wire system to protect the system from tampering distribution chain lightning. The analysis result of the ground, against the installation of wire showing the decreasing the number of thunderbolt from 43 time to be 28 times struck with forming an angle conservation 55o. So that it can be constructed in say succeeded in reducing the number of interference lightning and apply them to the system can be in feeders who have often have been affected.